ANALISIS DAMPAK PENGENAAN TARIF IMPOR KEDELAI BAGI KESUAHTERAAN MASYARAKAT (ANALYSIS ON THE IMPACT OF SOYBEAN IMPORT TARRIFF TOWARDS SOCIAL WELFARE) - Darsono, Darsono (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2009)
Since Indonesia removed import tarriff in 1998, the volume of soybean import rised up to 500% in 2004, which naturally become a burden to the national income and become a great hit towards national soybean production. In Februari 2005, the governmet re-enacted soybean import tariff at l0% to l5%. This study was aimed to: conduct a critical analysis towards the Government's new regulation of soybean import tarriff by analyzing its impact consumers' welfare as the producers, consumers' welfare, the Government's income, and society's welfare in general. The result was: based on the currency rate oJ'Rp.9,000/US, tariff regulation of 10% (citeris paribus) bring impact on the increase of the producer's surplus improvement, Government's income, and society's welfare but resulted in a decrease on consumers' surplus. An increase of tariff up to 27% is still recommended, especially at the currency rate depreciation of Rp. 9,000/U58. Yet, there are risks of decline in the farmer's normal profit and trade off of soybean field with other staple crops.